WHO REALLY IS THE POLICY PROBLEM: RETHINKING POLICY DESIGN - Terese Edwards (PEOPLE: International Journal of Social Sciences, 2026)
This presentation will explore the essential role that personal experiences should play in shaping and informing policy development. Effective policy design requires a thorough analysis of issues, potential solutions, and anticipated outcomes. While experts in policy research and implementation have established methodologies for framing problems, evaluating interventions, and projecting impacts, this approach often overlooks the perspectives of those directly affected by these issues and the informal aspects of the policy-making process. The presentation will highlight a collaboration between university research and civil society in Australia that began in 2019, showing how policy initiatives can prioritise and elevate the voices of those impacted, such as single mothers, while adhering to the university’s guidelines and ethical considerations. By showcasing recent examples, the presentation will illustrate how this methodology, combined with intentional framing, enhances overall effectiveness, particularly in addressing concerns about gender inequality.